2020
DOI: 10.1002/bit.27654
|View full text |Cite
|
Sign up to set email alerts
|

Temperature and oxygen level determine N2O respiration activities of heterotrophic N2O‐reducing bacteria: Biokinetic study

Abstract: Nitrous oxide (N2O), a potent greenhouse gas, is reduced to N2 gas by N2O‐reducing bacteria (N2ORB), a process which represents an N2O sink in natural and engineered ecosystems. The N2O sink activity by N2ORB depends on temperature and O2 exposure, yet the specifics are not yet understood. This study explores the effects of temperature and oxygen exposure on biokinetics of pure culture N2ORB. Four N2ORB, representing either clade I type nosZ (Pseudomonas stutzeri JCM5965 and Paracoccus denitrificans NBRC102528… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 61 publications
0
10
0
Order By: Relevance
“…Besides N 2 O reduction rates, microorganisms with low K m values, such as P. denitrificans and D. aromatica , could be useful in scavenging low concentrations of dissolved N 2 O. It is important to note, however, that the kinetics and O 2 sensitivity of N 2 O reducers can be influenced by environmental factors, such as the type of organic carbons ( 30 ) and temperature ( 31 ). Therefore, when selecting appropriate N 2 O reducers for engineering applications, their N 2 O reduction kinetics and O 2 sensitivity should be measured under environmentally relevant conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Besides N 2 O reduction rates, microorganisms with low K m values, such as P. denitrificans and D. aromatica , could be useful in scavenging low concentrations of dissolved N 2 O. It is important to note, however, that the kinetics and O 2 sensitivity of N 2 O reducers can be influenced by environmental factors, such as the type of organic carbons ( 30 ) and temperature ( 31 ). Therefore, when selecting appropriate N 2 O reducers for engineering applications, their N 2 O reduction kinetics and O 2 sensitivity should be measured under environmentally relevant conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Besides N 2 O reduction rates, microorganisms with low K m values, such as Pa. denitrificans and D. aromatica , could be useful in scavenging low concentrations of dissolved N 2 O. It is important to note, however, that the kinetics and O 2 sensitivity of N 2 O reducers can be influenced by environmental factors such as the type of organic carbons [28] and temperature [29]. Therefore, when selecting appropriate N 2 O reducers for engineering applications, their N 2 O reduction kinetics and O 2 sensitivity should be measured under environmentally relevant conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Azospirillum brasilense strains were also used as a microbial inoculant for N 2 O mitigation in soil. [27] Nevertheless, engineering applications of biological that the kinetics and O 2 sensitivity of N 2 O reducers can be influenced by environmental factors such as the type of organic carbons [28] and temperature [29]. Therefore, when selecting appropriate N 2 O reducers for engineering applications, their N 2 O reduction kinetics and O 2 sensitivity should be measured under environmentally relevant conditions.…”
Section: Nosz Structural Similaritiesmentioning
confidence: 99%
“…In the present study, it was observed that although DM15 and DM22 belong to the same genus of Pseudomonas, they performed significantly different N2O reducing abilities. Since it has been reported that environmental factors could lead to the functional differentiations of denitrifying bacteria, such as temperature, oxygen level, pH and C/N [23,26,29,30], whether the functional difference of these strains was related to environmental conditions? The results of the present study indicated that either under anaerobic and aerobic or varied temperature conditions, DM15 regardless performed higher N2O reducing ability than DM22, which suggested that environmental factors would not be the main reason for their differential N2O reducing abilities.…”
Section: Discussionmentioning
confidence: 99%
“…However, it was also indicated that some aerobic denitrifiers exhibited relatively strong N2O reducing efficiency under oxic condition [20,21], such as Pseudomonas, Azospirillum, Herbaspirillum, Marinobacter [22][23][24][25][26]. The suitable pH and temperature for N2O reducing isolates were between 6-8 and 15-35°C [27][28][29][30], respectively. Out of these ranges the N2O reducing activities were obviously restricted.…”
Section: Introductionmentioning
confidence: 99%